2020
DOI: 10.3390/ijms21103518
|View full text |Cite
|
Sign up to set email alerts
|

AMPK and the Need to Breathe and Feed: What’s the Matter with Oxygen?

Abstract: We live and to do so we must breathe and eat, so are we a combination of what we eat and breathe? Here, we will consider this question, and the role in this respect of the AMP-activated protein kinase (AMPK). Emerging evidence suggests that AMPK facilitates central and peripheral reflexes that coordinate breathing and oxygen supply, and contributes to the central regulation of feeding and food choice. We propose, therefore, that oxygen supply to the body is aligned with not only the quantity we eat, but also n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 233 publications
(343 reference statements)
0
13
0
1
Order By: Relevance
“…Mammalian ventilatory reflexes can be facilitated by the energy sensor, AMPK, which is 611 activated by an increasing AMP:ATP ratio (Evans, 2019;Evans and Hardie, 2020), also 612 implicating the involvement of mitochondrial operation. In locusts, the ventilatory motor pattern 613 changes induced by mitochondrial inhibition using sodium azide (chemical "anoxia") are 614 mimicked by AMPK activation using AICAR, although in the latter case there is no SD 615 (Rodgers-Garlick et al, 2011).…”
Section: Motor Patterningmentioning
confidence: 99%
“…Mammalian ventilatory reflexes can be facilitated by the energy sensor, AMPK, which is 611 activated by an increasing AMP:ATP ratio (Evans, 2019;Evans and Hardie, 2020), also 612 implicating the involvement of mitochondrial operation. In locusts, the ventilatory motor pattern 613 changes induced by mitochondrial inhibition using sodium azide (chemical "anoxia") are 614 mimicked by AMPK activation using AICAR, although in the latter case there is no SD 615 (Rodgers-Garlick et al, 2011).…”
Section: Motor Patterningmentioning
confidence: 99%
“…AMP has a major role in cellular metabolism, acting as a small molecule messenger that helps to integrate the rest of cellular metabolism with energy metabolism. Controlling the activity of AMP dependent protein kinase is one of the most important of those regulatory activities [9][10][11][12][13][14][15]. A dashed vertical line has been included in Figure 3B at the [AMP] f reported by Frederich and Balschi [3] to result in half maximal activity of AMPK under physiological conditions.…”
Section: Transformation Of Glyceraldehyde-3-phosphate To Pyruvatementioning
confidence: 98%
“…Consistent with the generic pathway described earlier, oxidative phosphorylation consists of a near equilibrium reaction coupled to ATP synthesis followed by an irreversible reaction that is also coupled to ATP synthesis. The initial near equilibrium reaction incorporates the first two energy coupling sites: NADH + 2 cyt c +3 +2 ADP + 2 Pi = NAD + + 2 ATP + 2 cyt c +2 (10) Transfer of two reducing equivalents from intramitochondrial NADH to oxidized cytochrome c (cyt c 3+ ) is coupled to the synthesis of 2 ATP. The dependence of the reactions on pH is not included in order to simplify the presentation.…”
Section: Energy (Atp) Production By Oxidative Phosphorylationmentioning
confidence: 99%
“…Other researchers have shown that the progression from acute to chronic HPH results from excessive repression of AMPK expression in the pulmonary vasculature during sustained chronic hypoxia. Hence, it seems plausible that cardiorespiratory adaptation to hypoxia at altitude and HPH induced by other factors may be driven by cell-specific changes in AMPK subunit expression and/or AMPK activity [ 159 ]. Figure 2 depicts the mechanisms implicated in the vasodilatory actions of AMPK.…”
Section: Hypoxic Pulmonary Hypertension (Hph)mentioning
confidence: 99%